The Saigon times weekly No 45 - '17 (1362) (Ho Chi Minh City Saigon times group, 2017)
Contents of the magazine presented about Inside Vietnam: foreign invesment,....; business: market, start up; living: expat life,......
Keywords: Tạp chí